Structuring Literatures - Joel Rey U. Acob (Humanistic Network for Science and Technology (HNST), 2019)
Literature regardless of the style and manner of inscription is aimed to connecting the dots and prints of every research. In the review process, literature review strengthen the claim of the researcher on the topic of interest. Authors penned salient attributes in the structure of research literature: 1) establishing degree of persuasiveness, 2) the process of naming literatures for review, 3) provenance, 4) methodology, 5) value-driven literature. Keywords: Literature review, Literature development, Issues of literature review